2012
DOI: 10.3109/13693786.2011.606850
|View full text |Cite
|
Sign up to set email alerts
|

Association between indoor fungi in Delhi homes and sensitization in children with respiratory allergy

Abstract: Indoor fungi are potential sensitizing agents in children and their detection and quantification in indoor air are important in the diagnosis and environmental management of fungal allergies. The objective of this investigation was to assess the prevalence of fungal allergies in children in Delhi and to study the association between mold counts in the homes of children and their sensitization to respective fungal extracts. Fungal concentrations and seasonality were studied at two-week intervals for one year us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Local grass pollination occurred through the summer and fall, and so the sensitization rate might have progressively decreased from the highest in fall to the lowest in spring. Molds, particularly A. fumigatus , showed a significantly higher sensitization rate in the winter, consistent with previous reports26,27 that have shown that the indoor molds Penicillium and Aspergillus were dominant in indoor air in the winter.…”
Section: Discussionsupporting
confidence: 92%
“…Local grass pollination occurred through the summer and fall, and so the sensitization rate might have progressively decreased from the highest in fall to the lowest in spring. Molds, particularly A. fumigatus , showed a significantly higher sensitization rate in the winter, consistent with previous reports26,27 that have shown that the indoor molds Penicillium and Aspergillus were dominant in indoor air in the winter.…”
Section: Discussionsupporting
confidence: 92%
“…This can be explained by the increased exposure of aeroallergens that evoked allergen sensitization even without any genetic predisposition. Night time onset of symptoms compared to daytime onset by most of the patients is similar to earlier reports [23]. …”
Section: Discussionsupporting
confidence: 79%
“…Dampness in the living place has already been reported as one of the major causes of aeroallergen sensitization [23]. In our study, we found people who reside in damp houses (whether new or old) were more prone to allergen sensitization.…”
Section: Discussionsupporting
confidence: 65%
“…From a study in Delhi, a correlation between skin positivity to different fungal extracts and specific IgE to the respective fungi in the sera was recorded in the range of 33–100%. 57 However, in a study performed in the united Kingdom, the concordance rates for individual fungi varied from 14 to 56% with an average of only 40%. Highest concordance (56%) was reported for Alternaria ; and only 29% was observed for Penicillium , which is in compliance with our study.…”
Section: Discussionmentioning
confidence: 97%